2015
DOI: 10.1002/jor.23126
|View full text |Cite
|
Sign up to set email alerts
|

Carpal arch and median nerve changes during radioulnar wrist compression in carpal tunnel syndrome patients

Abstract: The purpose of this study was to investigate the morphological changes of the carpal arch and median nerve during the application of radiounlarly directed compressive force across the wrist in patients with carpal tunnel syndrome. Radioulnar compressive forces of 10 N and 20 N were applied at the distal level of the carpal tunnel in 10 female patients diagnosed with carpal tunnel syndrome. Immediately prior to force application and after 3 minutes of application, ultrasound images of the distal carpal tunnel w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 32 publications
(97 reference statements)
0
26
0
4
Order By: Relevance
“…CAW values during widening always remained lower than the length of the TCL itself, indicating the TCL did not assume a tensioned state. Narrowing of CAW has been shown to increase the volar area of the carpal tunnel in previous biomechanical studies (Li et al, 2013; Marquardt et al, 2016; Marquardt et al, 2015). The reduction in CAW was maximized in radial volar direction (at 138° from 25.1 to 24.4 mm).…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…CAW values during widening always remained lower than the length of the TCL itself, indicating the TCL did not assume a tensioned state. Narrowing of CAW has been shown to increase the volar area of the carpal tunnel in previous biomechanical studies (Li et al, 2013; Marquardt et al, 2016; Marquardt et al, 2015). The reduction in CAW was maximized in radial volar direction (at 138° from 25.1 to 24.4 mm).…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, another in vivo study evaluating the pinching of the index finger against thumb reported a decrease of 0.8 mm in CAW and an increase of 5.1 mm 2 in volar area (Shen and Li, 2013). Several other studies also have shown that an increase in volar area results from the narrowing of the CAW (Li et al, 2013; Li et al, 2011; Li et al, 2009; Marquardt et al, 2016; Marquardt et al, 2015). The current FE model demonstrated that changes in the dorsal area were smaller than those of volar area, indicating that during narrowing the formation of the ligament arch contributes to an increase in the overall area of the tunnel.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations